Examining the linkage among market orientation, learning orientation and innovation performance: The mediation role of knowledge management - Putra, Anak Agung Gede Andy Pratama; Wahyuni, Ni Made; Yasa, Putu Ngurah Suyatna; Giantari, I Gusti Ayu Ketut (International research journal of management, IT and social sciences, 2020)
Small and medium enterprises (SMEs) exports contribute as a driver of the global economy and a source of economic growth. In the global era, to main a competitive advantage, SMEs need to produce behavior to ensure the feasibility of innovation performance. The purpose of this study is to investigate the relationship between market orientation, learning orientation, and knowledge management on innovation performance. The research method uses a research design cross-section. The study population includes all export-oriented manufacturing industries. SMEs and is registered in the Bali Provincial Industry and Trade Office database (2019). A total of 94 senior managers are SME interested in participating in the survey. Seven hypotheses are presented related to market orientation, learning orientation, knowledge management, and innovation performance, and the mediating effect of knowledge management. Structural equation model based Partial least square (SEM-PLS) is used to test the hypothesis. These findings reveal that learning orientation in manufacturing SME operation contributes to knowledge management. Knowledge management plays a mediating role in the relationship between market orientation and learning orientation on innovation performance. These results contribute additional insights to managers and policymakers about the concepts of market orientation, learning orientation, and knowledge management to achieve innovation performance.